Enseigner en contexte de diversité ethnoculturelle : des leçons de l’expérience à transmettre - Audet, Geneviève; Gosselin-Gagné, Justine (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
The student population in Quebec is increasingly characterized by significant ethnocultural, linguistic, and religious diversity. However, the degree to which schools take this diversity into consideration remains varied. This article presents the results of a research project that aims to shed light on the professional knowledge that teachers have developed regarding pedagogical intervention with students from immigrant backgrounds. The participants’ stories allowed us to identify various lessons that they learned from their work experience in an ethnoculturally diverse context. In this article, these different lessons have been organized around three themes: a role to play, attitudes to demonstrate, and experience and collegiality to develop. The analysis of the participants’ stories of practice highlights experiential lessons which could be transmitted to other teachers in initial or even continuing training.